Radionuclide concentrations, ratios, and derived ages of massive sulfides from ODP Leg 139 and Leg 169 sites, supplementary data to: Scholten, Jan; Lackschewitz, Klas S; Marchig, Vesna; Stoffers, Peter; Mangini, Augusto (2000): 230Th/234U and 231Pa/235U disequilibria in massive sulfides from the Bent Hill area (Legs 139 and 169). In: Zierenberg, RA; Fouquet, Y; Miller, DJ; Normark, WR (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 169, 1-15 - Scholten, Jan; Lackschewitz, Klas; Marchig, Vesna (PANGAEA - Data Publisher for Earth & Environmental Science, 2000)
Massive sulfide samples from the Bent Hill area were analyzed for 230Th/234U and 231Pa/235U disequilibria. Apparent ages calculated from these ratios are between 8.2 and >300 ka. Concordant ages were found for only three samples that originate near the surface from the clastic sulfide zone and suggest "true" ages of between 8.5 and 16.0 ka (mean of 230Th and 231Pa ages). The uranium vs. depth distribution in the Bent Hill Massive Sulfide deposit suggests an open system for uranium for the deeper part of the deposit, which was probably caused by extensive recrystallization processes inhibiting true age determinations.